Criminology: explaining crime and its context - Brown, Stephen E. (Routledge, 2024)
"Criminology: Explaining Crime and Its Context, Eleventh Edition, offers a broad perspective on criminological theory. It provides students of criminology, criminal justice, and sociology with a thorough exposure to a range of theories about crime, contrasting their logic and assumptions, but also highlighting efforts to integrate and blend these frameworks. In this new edition, the authors have incorporated new directions that have gained traction in the field, while remaining faithful to their criminological heritage. Among the themes in this work are the relativity of crime (its changing definition) with abundant examples, historical roots of criminology and the lessons they have provided, and the strength and challenges of applying the scientific method. This revision offers new chapters on critical theory and on life-course criminology It is updated throughout to reflect current trends in criminological theory and data. With chapters both updated to reflect recent developments in the field and made easier to digest, this text is essential reading for students of criminology, criminal justice, sociology, and related fields"--